Factor x3 + x2 + x + 1 by grouping. What is the resulting expression?
2 answers:
To factor by grouping, you group up the 1st 2 terms together and the last 2 terms together and then factor those pieces.
(x^3 + x^2) + (x + 1)
x^2(x + 1) + 1(x +1) - now factor out the (x + 1)
(x + 1)(x^2 + 1) - final answer
Answer: answer is C.
Step-by-step explanation:
You might be interested in
The answer is 0.5. I hope this is helpful.
The answer is 1.5 months
explanation:
5/2 = 2.5
15/4 = 3.75
2.5 per month
3.75 per x months
x = (3.75×1)/2.5
x = 3.75/2.5
x = 3/2 = 1.5 months
The answer is 60. You can find this out by finding the least common multiple of 10 and 12, which is 60 because 10x6=60 and 12x5=60. Hope this helps :)
Answer:
![They'll \: be \: on \: the \: circle:](https://tex.z-dn.net/?f=They%27ll%20%20%5C%3A%20be%20%20%5C%3A%20on%20%20%5C%3A%20the%20%5C%3A%20%20circle%3A)
![(x+3)^2+(y+6)^2=25](https://tex.z-dn.net/?f=%28x%2B3%29%5E2%2B%28y%2B6%29%5E2%3D25)
![x=1](https://tex.z-dn.net/?f=x%3D1)
![(y+6)^2=9](https://tex.z-dn.net/?f=%28y%2B6%29%5E2%3D9)
![y + 6 = 3](https://tex.z-dn.net/?f=y%20%2B%206%20%3D%203)
![y = -3](https://tex.z-dn.net/?f=y%20%3D%20-3)
![(1,-3)](https://tex.z-dn.net/?f=%281%2C-3%29)
![y + 6 = -3](https://tex.z-dn.net/?f=y%20%2B%206%20%3D%20-3)
![y = -9](https://tex.z-dn.net/?f=y%20%3D%20-9)
![(1,-9)](https://tex.z-dn.net/?f=%281%2C-9%29)
Step-by-step explanation:
![Thank \: you!!!!!!](https://tex.z-dn.net/?f=Thank%20%5C%3A%20%20you%21%21%21%21%21%21)
I believe this would be the solution.